Enhancement of Microalgal Metabolite Production through Euglena sp. Local Strain and Glagah Strain Consortia (Biosaintifika: Journal of Biology & Biology Education, 2023)
Euglena sp. is green microalgae in an acidic environment (pH 2.5-3.5). Euglena sp. has recently been developed widely in industry because of its capability to produce lipids that can be utilized to synthesize biofuel. Microalgae is a potential source of biodiesel, especially in the form of a consortium culture. One of the microalgae consortium cultures that have been explored is the nature consortium microalgae of Glagah strain.  The Glagah consortia were isolated from Lagoon in the Glagah Beach, Kulonprogo, Yogyakarta. This study aimed to determine the total production of biomass, lipids, carbohydrates, and proteins of mixed culture of Glagah strain consortium and Euglena sp. as biodiesel substrate. The biomass test was measured using the dry weigh method using a filtration vacuum pump kit, lipids were measured using the Blight Dryer method by adding chloroform and methanol as solvents, carbohydrates were measured using the Sulfur Phenol Acid method by adding Phenol and sulfuric acid (H2SO4), and proteins were measured using the Bradford method by adding SDS and Bradford’s solution. The total production and productivity of biomass, lipids, carbohydrates, and proteins showed that the mixed culture of Glagah strain consortium with Euglena sp. was higher than the Glagah strain consortium. It reached 0.410 g/L; 0.253; 0.856 g/L; and 0.623 g/L. Therefore, it could be concluded that the mixed culture of the Glagah strain consortium with Euglena sp. could increase the production of biomass, lipids, carbohydrates, and protein up to two times that of the Glagah strain consortium so that this mixed culture treatment could be used as a reference in microalgae cultivation for biodiesel.